Thickness and Material Analysis of the Radiation Shielding in 30 MeV Cyclotron Room for BNCT using Particle and Heavy Ion Transport code System (PHITS) - Trixie K, Nindya Karissa (2023)
Boron Neutron Capture Therapy (BNCT) is a cancer therapy developed using cyclotron-based research with 30 MeV. High energy in this installation can endanger workers and the public nearby. Radiation shields are essential to prevent accidents from radiation exposure above safety limits, particularly in the high-energy cyclotron room with a higher risk of radiation dose leakage. Constructing a radiation shield for the cyclotron room includes selecting materials and determining shield thickness. Materials tested include concrete, barite concrete, and boron concrete. Dose rate calculations were executed using a T-track tally in the Particle and Heavy Ions Transport Code System (PHITS) program. Based on the research results, the radiation shielding of the three materials shows a dose rate below the standard limit of 0.25 µSv/h allowed by BAPETEN and ICRP 60. Concrete has a maximum dose of 0.248 µSv/h with a thickness of 290 cm, barite concrete has a dose of 0.22 µSv/h with a thickness of 226 cm and boron concrete has a dose of 0.18 µSv/h with a thickness of 197 cm. Therefore, all three materials can be used as options for building radiation shields, each with its own advantages and disadvantages.